Digital diplomacy and its role in reshaping contemporary international relations - Hind Yousef Azem; Sayel Fallah Al-Sarhan (International Journal of Law Research and Studies, 2026)
This study aimed to shed light on the concept of digital diplomacy and demonstrate its pivotal role in reshaping the features of contemporary international relations, in light of the massive technological boom the world witnessed between (2000-2025). The study sought to address a primary problem concerning how digital platforms and technological tools affect traditional foreign policy instruments and the extent of their contribution to enhancing the soft power of states. To achieve the study’s objectives, the researcher employed a descriptive-analytical approach to review and analyze contemporary political literature and previous studies. The study reached several key results, most notably: digital diplomacy has become a strategic tool that transcends simple communication to become a means for crisis management and immediate international image-building. Furthermore, the study revealed that the digital transformation has expanded the circle of international actors to include non-state actors, while giving rise to new security and sovereign challenges related to cybersecurity and disinformation. The study concluded with recommendations emphasizing the necessity of strengthening the digital infrastructure of diplomatic institutions and developing international legal frameworks to regulate diplomatic work in cyberspace, especially with the integration of Artificial Intelligence (AI) technologies into political decision-making.